Behavior of moment‐resisting tall steel structures exposed to a vertically traveling post‐earthquake fire. (14th August 2013) - Behnam, Behrouz; Ronagh, Hamid R.
SUMMARY An investigation is performed on a 10‐story moment‐resisting steel structure designed to the Life Safety level of performance of the Federal Emergency Management Agency (FEMA) 356 code by exposing it to post‐earthquake fire (PEF). The fire curve is accounted for using the natural fire method, and the fire is subjected to the floors vertically in three different scenarios: (a) fire initiated from the first floor, (b) fire initiated from the fourth floor and (c) fire initiated from the seventh floor. A delay of 5 minutes and 25 minutes are considered for spreading the fire between the floors. To make a comparison between the results, a concurrent fire is also considered for the fire analysis. The results indicate that the PEF resistance of the frame exposed to the concurrent fire and the 5 minutes delay is much lower than that with a delay of 25 minutes. The results also show that subjecting the frame to a delayed fire of 25 minutes leads to the collapse of the frame during cooling phase, whereas in the other scenarios, the frame collapses during heating phase. As a result, more considerations need to be implemented in the codes on top of that for the PEF itself and that is the appropriate rate of spread of fire between floors. Copyright © 2013 John Wiley & Sons, Ltd.